(untitled) (Bioscience Journal, 2023)
This article aims to associate patient-reported pain intensity in the immediate seven days after dental implant surgery with surgical factors, sex and patient age. The sample was composed of 108 patients from a dental school in southern Brazilian, between 2018 and 2020. The variables torque, pre- and postoperative medication, healing of first and second intention, gender, age, number of quadrants, number of implants and type of surgery were related to the outcome pain. Pain was reported every day by the patient until the seventh day after surgery, using a visual analogic scale (VAS). Univariate Poisson regression models were used to assess the relationship among pain and the factors. Rate ratios were obtained with 95% of confidence intervals. Overall pain was reported as moderate/intense (VAS: 3-10) by 30.56% of patients, mild pain (VAS: 1-3) by 55.56%, and no pain symptoms were reported by 13.89% of patients. Individuals which the implants were installed with high torques (50-80 N) showed more pain (p=0.03) compared to patients which the implants were installed with regular torque (30-45 N). The other factors evaluated were not significant. The torque was the most relevant factor related to pain among the evaluated by the study. High torque generates more postoperative pain than lower torque. The factors gender, age, number of operated quadrants, number of installed implants, type of surgery and pre and postoperative analgesic did not interfere in the patient’s pain during the first week after surgery.